Enhanced energy storage in relaxor (1-x)Bi0.5Na0.5TiO3-xBaZryTi1-yO3 thin films by morphotropic phase boundary engineering - Herbert Kobald; Alexander M. Kobald; Ivana Panzic; Marco Deluca (Communications Materials)
Abstract Perovskites at the crossover between ferroelectric and relaxor are often used to realize dielectric capacitors with high energy and power density and simultaneously good efficiency. Lead-free Bi0.5Na0.5TiO3 is gaining importance in showing an alternative to lead-based devices. Here we show that (1-x)Bi0.5Na0.5TiO3 – xBaZr y Ti 1-y O3 (best: 0.94Bi0.5Na0.5TiO3 -0.06BaZr0.4Ti0.6O3) shows an increase of recoverable energy density and electric breakdown upon chemical substitution. In thin films derived from Chemical Solution Deposition, we observed that polarization peaks at the morphotropic phase boundary at x = 0.06. While Zr substitution results in reduced polarization, it enhances both efficiency and electric breakdown strength, ultimately doubling the recoverable energy density and the metallization interface by lowering surface roughness. Our dielectric capacitor shows <3% deviation of energy properties over 106 cycles. A virtual device model of a multilayer thin film capacitor (7.25 mJ recoverable energy) was used to compare its performance to already in use multilayer ceramic capacitors.